Review of the Air Transport Sector in Tajikistan - World Bank (Washington, DC, 2014)
The aviation sector in Tajikistan is struggling today under a very restrictive air transport policy. Together with it, the whole economy of the country is being deprived from the derived benefits of better connectivity, such as trade, travel, and technology transfer. While maintaining safety as the highest single priority, the Government recognizes that the air transport policy should allow for a liberalization of the markets, allowing better connectivity with more efficient services at lower prices. The only possible way to ensure the implementation of a liberalized policy, an appropriate institutional framework needs to be in place, allowing for the complete separation between the policy maker, the technical regulator and the operation. The airline, the airport, and the air traffic control will be separated in order to assure truly competition. Currently, all operations activities are concentrated at Tajikistan State Airlines (TSA). TSA is today an inefficient company that provides poor service to its customers at prices that are high and provide an involuntary price umbrella for the competition. Its present existence was granted by a protective environment, where a concentrated institutional framework allowed regulation to be tinted by policy motivations. Instead of promoting transparency in accounting and efficiency in operations, there have been initiatives to grant further loans that would end up fueling costs and inefficiencies, while not achieving any of the promised results. At bottom, all these inefficiencies are paid by the migrant worker community that travels to Russia at unjust air fares, representing a substantial part of their earnings. A new policy that would liberalize the sector will promote efficiency and lower the costs of travel, relieving the tax on a huge mass of people, which is crucial to the economy of Tajikistan.